38.1k views
5 votes
What is the solution to the equation ? -4(2x+3) = 2x+6-(8x+2)

2 Answers

3 votes

Answer:


x=-8

Explanation:


\mathrm{Expand\:}-4\left(2x+3\right):\quad -8x-12


\mathrm{Expand\:}2x+6-\left(8x+2\right):\quad -6x+4
-8x-12=-6x+4

Add 12 to both sides:
-8x-12+12=-6x+4+12


-8x=-6x+16

Add 6x to both sides:
-8x+6x=-6x+16+6x


-2x=16

Divide both sides by -2:
(-2x)/(-2)=(16)/(-2)

Simplify.

Hope this helps!!

User Radan
by
5.2k points
5 votes

Answer:

x=-8

Explanation:

-4(2x+3) = 2x+6-(8x+2)

The first step is to distribute the -4 and the -1

-4*2x+-4*3 = 2x+6 -8x-2

-8x-12 = 2x+6-8x-2

Combine like terms

-8x-12 = -6x+4

Add 8x to each side

-8x+8x-12 = 8x-6x+4

-12 = 2x+4

Subtract 4 from each side

-12-4 = 2x+4-4

-16 = 2x

Divide by 2

-16/2 = 2x/2

-8=x

User Vitali Kaspler
by
5.8k points